Pendekatan Pedagogic dan Skema Pembelajaran Pendidikan Kewarganegaraan untuk Mempromosikan Kewarganegaraan Ekologi - Fitriah Artina; Muhammad Amin (Universitas Hamzanwadi, 2024)
Environmental problems as a world issue require the importance of preparing citizens to have the ability to prevent environmental problems. This research aims to present a study of pedagogical approaches and citizenship education learning schemes in strengthening the integration of ecological citizenship into education as an effort to provide a foundation for citizenship education to develop ecological citizenship in schools. This research uses a comprehensive literature review research method, involving analysis and synthesis of findings from various literature to gain an understanding of the ecological citizenship education learning scheme. The research results show that the pedagogical landscape of ecological citizenship education can be packaged in learning approaches (1) place-based learning; (2) problem-based learning; (3) environmental justice pedagogy; (4) ecological citizenship education; (5) action competency learning; (6) learning to serve; (7) participatory action research; (8) socio-scientific inquiry-based learning (SSIBL). the pedagogical approach to ecological citizenship education includes six (6) stages: (1) inquiry; (2) planning action; (3) critical and active involvement; (4) community participation and networking on a scale (local, national, global), (5) maintaining environmental and social change, and (6) evaluation and reflection.